Concep????o e implementa????o da tecnologia r??dio cognitivo e adaptativo sobre fibra - Raimundo Neto, Eg??dio (2014)
This work proposes the concept and reports the implementation of the architecture ACRoF, which stands for Adaptive and Cognitive Radio over Fiber. It is aimed to deal with the new demands for convergent networks by means of simultaneously providing the functionalities of radiofrequency spectrum sensing, dynamic resource allocation and centralized network processing capability. Furthermore, it enables the use of optically controlled reconfigurable antennas and radio over fiber technology. This concept is based on a central office with multiband spectrum sensing and dynamic resource allocation functionalities, and simple remote antenna units composed by optically controlled reconfigurable antennas for data transmission and a broadband antenna for sensing the frequency spectrum. The architecture performance has been evaluated in a geographically distributed optical-wireless network under real conditions and for different fiber-optic lengths. Experimental results demonstrate reach extension of more than 40 times and an enhancement of more than 30 dB in the carrier to interference plus noise ratio parameter when compared to a conventional wireless network.